Effects of Papain Concentration and Hydrolysis Time on Degree of Hydrolysis and Glutamic Acid Content of Apple Snail Hydrolysate - Dedin Finatsiyatull Rosida; Anugerah Dany Priyanto; Andre Yusuf Trisna Putra (Nusantara Science and Technology Proceedings, 2020)
Umami taste enhances the high palatability in cuisine by the presence of high level of glutamic acid content. This savoriness compound could get from fermentation and hydrolysis process. Generally, consumer perception thinks preferable natural sources due to food safety issues. Apple snail (Pila ampullacea) is known as abundant wildlife containing high protein source. The most popular protease in Indonesia is papain, which was used to generate the apple snail hydrolysate. The objective of this research is to define the specified condition based on papain concentration and hydrolysis time to produce umami taste from apple snail. Those two variables showed a significant effect on the degree of hydrolysis and glutamic acid content of apple snail hydrolysate, therefrom the data were several various values in the lowry method and ninhydrin colorimetry, respectively. The established condition resulting in a degree of hydrolysis and glutamic acid content was as high as 56.56 ± 1.65% and 95.34 ± 0.13 ppm. The study concluded that papain within certainly condition denotes free amino acid in releasing of umami taste. Furthermore, this research will be applied as flavour enhancers, commonly known as monosodium glutamate (MSG). Also, this study promotes a natural source as safer flavor enhancers, utilization of potential local commodity, and can compete with the commercial ones.